On-Surface Synthesis of Ethynylene-Bridged Anthracene Polymers - Sánchez-Grande, Ana; de la Torre, Bruno; Santos, José; Cirera, Borja; Lauwaet, Koen; Chutora, Taras; Edalatmanesh, Shayan; Mutombo, Pingo; Rosen, Johanna; Zbořil, Radek; Miranda, Rodolfo; Björk, Jonas; et al. (Angewandte Chemie (International ed. in English), 2019)
Engineering low-band-gap π-conjugated polymers is a growing area in basic and applied research. The main synthetic challenge lies in the solubility of the starting materials, which precludes advancements in the field. Here, we report an on-surface synthesis protocol to overcome such difficulties and produce poly(p-anthracene ethynylene) molecular wires on Au(111). To this aim, a quinoid anthracene precursor with =CBr2 moieties is deposited and annealed to 400 K, resulting in anthracene-based polymers. High-resolution nc-AFM measurements confirm the nature of the ethynylene-bridge bond between the anthracene moieties. Theoretical simulations illustrate the mechanism of the chemical reaction, highlighting three major steps: dehalogenation, diffusion of surface-stabilized carbenes, and homocoupling, which enables the formation of an ethynylene bridge. Our results introduce a novel chemical protocol to design π-conjugated polymers based on oligoacene precursors and pave new avenues for advancing the emerging field of on-surface synthesis.
Keywords: acenes; polymers; scanning probe microscopy; surface chemistry; low-band-gap semiconductors